The Effect of Matos Soil Stabilizer on Mechanical Properties of Soil Stabilized with Cement - Ardhana, Praditya; Aprianto; Bachtiar, Vivi; Rustamaji, R M; Priadi, Eka (Engineering Forum of Western Indonesian Government Universities Board (Forum Teknik, BKS-PTN Wilayah Barat) Indonesia, 2024)
In pavement construction, it consists of subgrade, foundation layer and overburden. In working on landfill, the quality of the landfill can be improved by stabilization. Stabilization is a way to improve the properties and parameters of the soil, so that the soil is suitable or qualified to be used according to its function. One of the ways to stabilize soil is by chemical stabilization. In this research using additives such as fly ash & matos soil stabilizer. The soil samples were taken from Peniraman Quarry, Mempawah Regency. Also, the fly ash used comes from the waste of Paiton power plant, Probolinggo Regency. The tests carried out were testing the physical properties of the soil. The results obtained were then adjusted to the lower foundation layer of the road with specifications based on the 2018 General Specifications, Road and Bridge Construction Work (Revision 2). The test was carried out with a mixture of 10% fly ash and variations of matos soil stabilizer 2 - 8%, stabilization was carried out with a curing period of 0 - 14 days. From the results of the soil test, the plasticity index was found to be 14.252%. From the test results of the highest mixture variation, which is a mixture of soil + 10% fly ash + 8% matos soil stabilizer with a curing period of 14 days. The test results obtained a plasticity index of 7.295%, so it can be concluded that the higher the percentage of matos soil stabilizer used, the plasticity index value of the soil decreases and has met the requirements in the construction of the lower foundation layer of the road (B class).